An exploratory study on the link between sibling relationships and friendship quality - Alıcı, Asya. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Sibling and friend relationships of emerging adults have been rarely studied compared to parent-child relationships. This study is primarily designed to explore the link between sibling relationship qualities and best-friendship qualities of emerging adults in Turkey, by investigating the moderator role of birth order and gender on this link. It is aimed to test which one of the carryover, compensation, and segmentation models will be supported by the current data. 213 college students between 18-25 years of age filled out an online surveys. Regression analysis showed that sibling relationship quality in adulthood was a predictor friendship quality. In addition to the higher quality of sibling relationships, being a woman, more frequent contact with the best friend, and residing in the same city with the sibling positively predicted friendship quality. Childhood sibling relationship quality was positively associated with friendship quality, although it was not a significant predictor in presence of adulthood sibling relationships. A relationship between birth order and friendship quality could not be found. Results showed evidence for the carryover model. The findings of the study were discussed within the framework of carryover model as well as considering the cultural context and emerging adulthood period of development.
Keywords: Siblings.; Friendship.